Livelihood Resilience of Rural Crop Farmers in the Face of Recurring Farm Theft; Evidence from Nigeria - Tunde ADEBISI; Festus ASAMU; Ogadimma ARISUKWU; Bamidele RASAK (Communications of International Proceedings, 2020)
Farming, like every other livelihood is not without its challenges. 21st century Africa has witnessed an increasing theft of farm produce and in some cases, the murder of farmers. The reality of farm theft in rural communities poses several questions about its prevalence, consequences, and farmers’ responses. Through a qualitative lens, this study investigates how and why rural crop farmers have remained interested in farming despite recurring farm theft. Eighteen (18) crop farmers were engaged in a semi-structured interview session. Through the discourse analysis approach, result showed five (5) major factors responsible for farmers’ livelihood resilience in the study locale; Tradition, Income, Health, Poverty, and Prestige. As such it is recommended that focus should be on improving such factors.
Keywords: Crop Farming; Livelihood Resilience; Farm theft